Potential Strategies for Overcoming Barriers to Career Transition Among Students with Visual Impairments - Eseadi, Chiedu (COUNS-EDU: The International Journal of Counseling and Education, 2023)
The visually impaired group remains among the most unemployed despite laws designed to facilitate employment opportunities for the disabled population. This review article presents potential strategies for overcoming barriers experienced by students with visual impairments (VIs) during their career transition. An integrative literature review was employed by the authors. The integrative literature review allows authors to produce new frameworks and perspectives on a topic from a range of existing research data and ideas in a significant manner. Results of the literature review suggest that public education, adequate transportation and mobility skills, proper assessment of the students' skill development, the acquisition of relevant social and independent-living skills, adequate training for rehabilitation service providers, adequate access to prints, collaboration among professionals, and early career education and work experience are some of the strategies that can be adopted to help students with VIs overcome most of the challenges they experience in their career transition journey. Adopting the strategies discussed in this article may lead to a successful career transition for these students. One of the implications of this paper is that visually impaired students should be able to adapt to the career environment by acquiring relevant skills and being open to opportunities. Also, specialized job training and placement might make it easier for visually impaired students to find competitive work after earning an academic degree and raise their chances of embarking on a successful career path.